Screening North American plant extracts in vitro against Trypanosoma brucei for discovery of new antitrypanosomal drug leads. Issue 1 (December 2016) - Jain, Surendra; Jacob, Melissa; Walker, Larry; Tekwani, Babu
Abstract Background Human African Trypanosomiasis (HAT) is a protozoan parasitic disease caused byTrypanosoma brucei . The disease is endemic in regions of sub-Saharan Africa, covering 36 countries and more than 60 million people at the risk. Only few drugs are available for the treatment of HAT. Current drugs suffer from severe toxicities and require intramuscular or intravenous administrations. The situation is further aggravated due to the emergence of drug resistance. There is an urgent need of new drugs that are effective orally against both stages of HAT. Natural products offer an unmatched source for bioactive molecules with new chemotypes. Methods The extracts prepared from 522 plants collected from various parts of the North America were screened in vitro against blood stage trypamastigote forms ofT. brucei . Active extracts were further screened at concentrations ranging from 10 to 0.4 μg/mL. Active extracts were also investigated for toxicity in Differentiated THP1 cells at 10 μg/mL concentration. The results were computed for dose–response analysis and determination of IC50/IC90 values. Results A significant number (150) of extracts showed >90 % inhibition of growth of trypomastigote blood forms ofT. brucei in primary screening at 20 μg/mL concentration. The active extracts were further investigated for dose–response inhibition ofT. brucei growth. The antitrypansomal activity of 125 plant extracts was confirmed with IC50 < 10 μg/mL. None of these active extracts showed toxicity against differentiated THP1 cells. Eight plants extracts namely, Alnus rubra, Hoita macrostachya, Sabal minor, Syzygium aqueum, Hamamelis virginiana, Coccoloba pubescens, Rhus integrifolia andNuphar luteum were identified as highly potent antitrypanosomal extracts with IC50 values <1 μg/mL. Conclusions Limited phytochemical and pharmacological reports are available for the lead plant extracts with potent antitrypanosomal activity. Follow up evaluation of these plant extracts is likely to yield new antitrypanosomal drug-leads or alternate medicines for treatment of HAT.